5PSQ-019 Switching from individualised nutrition to standardised or commercialised nutrition in newborns: are there any possibilities?. (March 2019) - Nisse, YE; Vidal, B; Lux, M; Hascoet, JM; Demoré, B
Abstract : Background: Newborns often require parenteral nutrition (PN). There are three possibilities from the least secure to the most secure: individualised, standardised and commercialised nutrition. New national guidelines for PN in newborns were published in April 2018. Purpose: To evaluate the substitutability potential of individualised nutrition by standardised or commercialised nutrition in a regional maternity hospital. Material and methods: This was a retrospective chart review of PN in newborns from August 2017 to January 2018. Requirements in the individualised nutrition were compared to the standardised formulations available in our hospital and to the commercialised nutrition adapted in preterm infants. Only glucose and electrolytes concentrations were compared because these are the only elements of our standardised nutrition formulations. Individualised PN were substitutable if the concentrations in standardised or commercialised PN were between −10% and +5% of the prescription. An addition was needed if a concentration was less than −10%. The individualised PN was not substitutable if one or more concentrations were greater than 5%. Results: This study included 2, 285 PN prescriptions concerning 263 newborns. There was 1241 individualised PN concerning 130 newborns, including 89% preterm. Medium gestational age was 30 (24; 41) weeks and medium weight was 1462 g (580; 3770). Medium prescription duration was 13 (1–54) days. One-thousand and eleven (81%) individualised nutrition could not be substituted in standardised or commercialised PN because of the inappropriate concentration of glucose or low concentration of electrolytes. None of the individualised nutrition can be substituted without addition. Two-hundred and thirty (19%) individualised nutrition could potentially be replaced: 187 by standardised nutrition and 43 by commercialised nutrition. These standardised or commercialised nutrition bags need, on average, 3.4 adjuncts of electrolytes to maintain the needs of the newborns. Three additions were authorised according to guidelines, so only 108 (9%) individualised nutrition could be substituted. Conclusion: The individualised PN rate of our maternity hospital is in line with the national PN rate. All substitutable individualised PN need some addition but there is no protocol to do that in our hospital. They were then always justified. There are two ways of improvement: use software that suggest the most adapted PN product; or define with the neonatologist which type of addition should be prioritised. References and/or acknowledgements: https://www.has-sante.fr/portail/jcms/c_2859140/fr/nutrition-parenterale-en-neonatologie-recommandation-de-bonne-pratique No conflict of interest.